Internal intestinal splinting with a soluble tube for the prevention of recurrent adhesion ileus - Jung, D; Lux, M; Werner, H H; Heymann, H (Chirurg, 1983)
An absorbable, non-toxic, easy gliding, cross-linked gelatine tube has been developed to prevent and to treat chronical adhesion ileus. The tube is patterned upon the interior intestinal splinting with long tubes. By doing a small enterotomy it was possible to splint the whole intestine in pigs or endangered parts within a few minutes. The flexible gelatine tube does not kink and is melting off from the surface. It prevents the intestine from kinking and does not cause any lesions even on previously damaged intestinal walls. Possible complications seen by insertion and extraction of conventional tubes were not observed.